The Relationship of Palliative Care to Quality of Life in the Elderly: A Literature Review - Muhamad Kafa Fahmi; Ns. Suri Salmiyati; Suratini, Suratini (Jurnal Multidisiplin Sahombu, 2025)
The increasing number of elderly people in Indonesia poses a serious challenge to the health and social sectors. Palliative care, which aims to improve the quality of life of the elderly, plays an important role in providing holistic care for patients facing chronic or terminal illnesses. This study aims to examine the relationship between palliative care and the quality of life of the elderly through a literature review. A literature search was conducted using two databases, Google Scholar and PubMed, with the keywords “Palliative Care,” “Quality of Life,” and “Elderly,” and selecting articles published between 2015 and 2022. A total of six articles met the inclusion and exclusion criteria, which were then systematically analyzed. The results of the analysis showed that palliative care contributes significantly to improving the quality of life of the elderly, especially through physical, psychological, social, and spiritual support. This care is proven to be effective both in direct intervention, homecare, and education to the elderly family. However, the limitation of relevant studies is a challenge in examining this topic in more depth. This research is a literature review conducted with a systematic approach. This study uses PICOST analysis to identify relevant literature. The analyzed literature was obtained from Google Scholar and PubMed databases, using the main keywords “Palliative Care,” “Quality of Life,” and “Elderly.” Inclusion criteria included articles published between 2015 and 2022, available in full text, and relevant to the topic. A total of 6 articles that met the inclusion criteria were used in this analysis. The results of the literature review show that palliative care can consistently improve the quality of life of the elderly. Aging, which causes a decrease in body function and endurance, makes the elderly more vulnerable to physical and psychological illnesses, so palliative care is very important to maintain their quality of life. According to WHO, quality of life includes physical, psychological, social, spiritual and environmental aspects. Of the 314 articles identified, 38 were duplicates and were excluded. After assessing the quality and appropriateness of the articles to the topic, 6 journals were obtained that met the criteria for systematic analysis. This selection flow is shown in the PRISMA flow chart. Palliative care can significantly improve the quality of life of the elderly, both in terms of physical, psychological, social, and spiritual aspects.